COVID-19 Vaccine-Induced Thrombotic Thrombocytopenia Leading to Stroke: An Extremely Rare but Possible Condition - Muhammad, Mubarak; Keng Loong, Shih; AbuBakar, Sazaly (Journal of Thai Stroke Society, 2024)
Coronavirus disease 2019 (COVID-19) vaccines remain the safest and most effective strategy against the COVID-19 pandemic. However, clinicians must be aware of any adverse events that might arise as a peculiar side effect in certain individuals. One of such extremely rare side effect that needs to be routinely integrated into the clinical decision-making arise from vector based COVID-19 vaccines that result in vaccine-induced thrombotic thrombocytopenia (VITT) and consequently stroke. Understanding any evolving information that relates with COVID-19 is critical to its successful containment and control. As such, unraveling the mechanism of VITT leading to stroke as well as its relevant clinical information is essential towards its successful integration into clinical guidelines. This short communication was therefore aimed at focusing on proposed mechanism through which stroke evolved from vaccine-induced thrombotic thrombocytopenia and its relevant clinical information for clinical practice. This study stresses the importance of being vigilant to the development of vaccine-induced thrombotic thrombocytopenia and stroke especially from the viewpoint of clinicians and other health care personnel. The phenomenon of VITT leading to stroke was also recommended for inclusion as a standard operation procedure in the standard clinical guidelines for the management of acute ischemic stroke.